ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEBUGARAN JASMANI DITINJAU DARI SCREEN TIME, AKTIVITAS FISIK DAN STATUS GIZI - Cahyono, Erdina Aldy; Wahjuni, Endang Sri; Wibowo, Sapto (JSES : Journal of Sport and Exercise Science, 2022)
This study aims to determine the dominant factors related to physical fitness in terms of screen time, daily physical activity, and the nutritional status of students. The research method used is descriptive research with a non-experimental quantitative approach. This research is ex post facto. The research was conducted at SMAN 2 Pasuruan with a total of 282 respondents consisting of 111 males and 171 females. The respondents were all tenth graders consisting of majors in Mathematics and Natural Sciences, Social Studies, and Cultural Language. The data analysis technique used in this study used chi square and multivariate linear regression analysis. The results of the study using bivariate analysis revealed that screen time and nutritional status did not have a significant relationship to the level of physical fitness, while physical activity had a significant relationship to the level of physical fitness. Multivariate analysis resulted that simultaneously screen time, physical activity, and nutritional status had a significant relationship to the level of physical fitness with an alpha value of 0,000 and physical activity was the dominant factor associated with the level of physical fitness as evidenced by an alpha value of 0,000 and a beta value of 0,4.